TREN ECO-FASHION DENGAN KAIN TENUN GEDOG TUBAN DALAM FASHION FOTOGRAFI CAMPAIGN - Firdaus, Nina; Purnama, Pongky Adhi; Candrastuti, Ratih (Institut Seni Indoensia Surakarta, 2021)
Currently eco-friendly trends among Indonesians are in great demand, eco-fashion is one example of the application of eco-friendly trends to maintain the environment by reducing textile waste. However, not many people know about eco-fashion trends. In the making of this Final Task the author will create a fashion campaign photo work, the strength in fashion photography itself is to be able to record images and communicate certain beauty and is expected to be able tokanlkan eco-fashion trends to the public at large. In this fashion campaign photo, the author takes the concept of Ayu Lan Praseja. Ayu Lan Praseja is taken from javanese language which has a beautiful and simple meaning. Ayu Lan Praseja’s concept tells about the nature and behavior of Javanese people inspired by javanese philosophy of “nrima ing pandum” which means to “take for granted whatever happens as God’s will or destiny”. The use of basic photography techniques is used in this Final Task and the result obtained by the author in this Final Task work is Fashion Campaign Photography that can convey the message that the author wants to convey, namely about Ayu Lan Praseja, with a mature concept and also good photo-taking techniques. Keywords: Eco-Fashion, Weaving Gedog Tuban, Fashion Photography.